Polymorphisms of TGF-beta1 in cystic fibrosis patients - Brazova, Jitka; Sismova, Kristyna; Vavrova, Vera; Bartosova, Jana; Macek, Milan; Lauschman, Hynek; Sediva, Anna (Clinical immunology (Orlando, Fla.), 2006)
There is a significant phenotypic variance among cystic fibrosis (CF) patients. Due to the role of TGF-beta1 in fibrotic processes we investigated its role in CF pathogenesis. TGF-beta 1 codons 10 and 25 were genotyped in 118 Czech CF patients and 268 controls by PCR-ARMS. Difference between CF and controls was found at codon 10, lower frequency of T/T homozygotes, and codon 25, higher frequency of G/C heterozygotes. We did not prove the association of TGF-beta1 polymorphisms and lung function in CF, however, the TT (codon 10)/GG (codon 25) genotype was preferentially associated with CF-related liver disease and diabetes. Independent of the TGF-beta1 genotype, production of cytokine was higher in patients than in controls with the notable exception of very low levels in Burkholderia cepacia complex colonized patients. In CF, both extremes, highest or lowest TGF-beta 1 production, were associated with impaired lung function.
Keywords: Male; Genotype; Infant; kojenec; Adult; polymorfismus genetický; Česká republika; ženské pohlaví; Czech Republic; cystická fibróza; předškolní dítě; Child, Preschool; Adolescent; Humans; Phenotype; dítě; genotyp; Child; Female; Transforming Growth Factor beta1; Cystic Fibrosis; Polymorphism, Genetic; dospělí; mužské pohlaví; mladiství; fenotyp; lidé; transformující růstový faktor beta1